A consumer decision-making process? Unfolding energy efficiency decisions of German owner-occupiers - Jan Paul Baginski; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2017)
The German housing stock needs substantial energetic retrofit to meet carbon reduction targets. Various instruments are available to motivate building owners to improve the energy efficiency of their dwellings. These instruments mainly focus on the economic issue of funding and financing energy efficient refurbishments as the decision is interpreted as a rational choice of an investment. Their success is rather low as the refurbishment rate stagnates around 1% per year for more than a decade. The objective of this study is to gain deeper insights into the decision-making of owner-occupiers regarding energy efficient refurbishments and to offer an adjusted framework to analyse the decision. A qualitative-explorative research approach is chosen, whereby in-depth interviews with independent energy advisers have been conducted. Results point out that the decision of owner-occupiers towards energy efficient refurbishment measures qualifies as an extensive consumer decision rather than a pure investment decision. The refurbishment measure implies high cognitive as well as emotional involvement. Owner-occupiers use several criteria to evaluate refurbishments, which alleviate monetary determinants. The standard process model of consumer decision-making, reaching from need recognition to post-purchase evaluation, qualifies for structuring the decision. It allows analysing drivers and barriers stepwise and deriving implications for activating homeowners and for promoting energy efficiency in each step. Current policies partly choose unrewarding argumentations to stimulate energy efficient refurbishments since they do not take all relevant factors of this consumer decision into account.
Keywords: 330; Energy efficient refurbishments; decision-making process; consumer purchase decision; energy efficiency policy